Diagnostic performance of ultrasound in assessing the extension of the disease in patients with suspicion of malignant ovarian tumor: correlation between ultrasound parameters and Fagotti's score. Issue 2 (7th September 2020) - Moruzzi, Maria Cristina; Bolomini, Giulia; Moro, Francesca; Mascilini, Floriana; Ficarelli, Silvia; Beneduce, Giuliana; Giudice, Maria Teresa; Pasciuto, Tina; Moroni, Rossana; Scambia, Giovanni; Fagotti, Anna; Testa, Antonia Carla
Abstract : Background: A radical surgical approach represents the mainstay treatment for gynecological malignancy, and preoperative staging of ovarian cancer is crucial. Ultrasound evaluation is widely recognized as the gold standard technique for the characterization of ovarian masses due to a high sensitivity for malignancy. In addition, its accuracy in defining intra-abdominal ovarian cancer spread has been previously proposed. Primary objective: To analyze the agreement between preoperative ultrasound examination and laparoscopic findings in assessing the extension of intra-abdominal disease using six parameters as described by Fagotti's score. Study hypothesis: When performed by expert examiners, ultrasound can be an accurate technique to assess tumor spread in ovarian cancer and therefore to predict surgical resectability. Trial design: This is a single-center prospective observational study. Patients with clinical and/or radiological suspicion of advanced ovarian or peritoneal cancer will be assessed with preoperative ultrasound and assigned a score based on the six Fagotti's laparoscopic score parameters. Each parameter will then be correlated with laparoscopic findings. Major inclusion/exclusion criteria: Eligible patients include women 18–75 years of age with clinical and/or imaging suggestive of advanced ovarian or peritoneal cancer, and an ECOG performance status 0–3. Primary endpoints: Sensitivity and specificity of ultrasound in detecting carcinomatosis, using the parameters of Fagotti's score as a reference standard. Agreement between preoperative ultrasound examination and laparoscopic findings in assessing the extension of intra-abdominal disease as described in Fagotti's score. Sample size: 240 patients. Estimate dates for completing accrual and presenting results: The accrual started in January 2019. Enrollment should be completed approximately by October 2020 and the results will be analyzed by December 2020. Trial registration: The study received the Ethical Committee approval on July 19 2018 (Protocol 28967/18 ID:2172).